Recent developments in South African Jesus research: From Willem Vorster to Andries van Aarde - Aarde, Andries van (Hervormde teologiese studies, 1993)
In the previous article (see HTS 49/3) the work of Andrie du Toit and Willem Vorster on historical Jesus research were discussed. In this article Andries van Aarde’s work is discussed under the following topics: Jesus as a social outcast, Herodian Palestine in macrosociological perspective, the historical Jesus and engaged hermeneutics, and the ‘fatherless’ Jesus. In conclusion, the kind of influence that South African Jesus research is subjected to or stimulated by is shown.